DIABETES-RELATED SEXUAL DYSFUNCTION AND ITS ASSOCIATION WITH MICROVASCULAR COMPLICATIONS: A STUDY FROM TERTIARY CARE CENTER IN SOUTH KERALA - PAUL, AJAY; ASOKAN, ATHULYA G. (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: (1) The objective of this study was to determine the frequency of sexual dysfunction (SD) among patients with Type 2 diabetes mellitus attending the General Medicine and Endocrinology Department at a tertiary care center in south Kerala. (2) To assess the relationship between erectile dysfunction and the microvascular consequences of Type 2 diabetes. (3) To correlate SD with glycemic status. Methods: One hundred and twenty patients with Type 2 diabetes at a tertiary care center in south Kerala participated in the cross-sectional study. A questionnaire was employed to document demographic and glycemic status. The assessment tools utilized included the International Index of Erectile Function for male and the Female Sexual Function Index (FSFI) scoring questionnaire for females. The statistical analysis employed included unpaired t-tests for students and tests assessing the equality of proportions. Results: About 65% of patients with diabetes mellitus had SD. About 46% of female participants and 78.6% of male participants in the study population had SD. Duration of diabetes, poor glycemic status, and microvascular complications correlated with SD. Conclusion: SD is frequent in patients with Type 2 diabetes mellitus. Glycemic control determines the development of SD. It is advisable to screen patients with Type 2 diabetes mellitus for SD as a proactive measure for early intervention and management.